Determination of Hopelessness and Quality of Life in Patients with Heart Disease: An Example from Eastern Turkey - Karakurt, Papatya (Journal of religion and health, 2018)
This descriptive study was undertaken in order to determine hopelessness and quality of life among the patients with heart disease. No sampling was made, and 200 patients who were voluntary and were able to communicate were included in the study. The data of the study were collected using a personal information form that involved questions about patients' descriptive information and their diseases, Beck Hopelessness Scale and SF-36 Quality of Life Scale with a face-to-face interview technique. For the analyses of the data, percentages, means, t test, Kruskal-Wallis and Pearson's correlation analyses were used. It was identified 54% of them was male patients. It was seen that there were significant between income status and general health perceptions, hopelessness; and between health perceptions and vitality, general health perceptions, global quality of life, hopelessness (p < .05). It was also explored that there was a negative correlation between hopelessness levels of the cardiac patients and functioning status, general health perceptions and global quality of life. It was determined that the desperation levels of the patients were above the middle level, and the quality of life was low.